Improving the self-management of chronic pain : Coping with persistent Pain, Effectiveness Research in Self-management (COPERS) /: Coping with persistent Pain, Effectiveness Research in Self-management (COPERS). (September 2016) - Taylor, Stephanie J. C
No abstract available